A Feedback-Based Transmission for Wireless Networks with Energy and Secrecy Constraints. (8th February 2011) - Krikidis, Ioannis; Thompson, John S.; McLaughlin, Steve; Grant, Peter M.
Abstract : This paper investigates new transmission techniques for clustered feedback-based wireless networks that are characterized by energy and secrecy constraints. The proposed schemes incorporate multiuser diversity gain with an appropriate power allocation (PA) in order to support a defined Quality-of-Service (QoS) and jointly achieve lifetime maximization and confidentiality. We show that an adaptive PA scheme that adjusts the transmitted power using instantaneous feedback and suspends the transmission when the required power is higher than a threshold significantly prolongs the network lifetime without affecting the QoS of the network. In addition, the adaptation of the transmitted power on the main link improves the secrecy of the network and efficiently protects the source message from eavesdropper attacks. The proposed scheme improves network's confidentiality without requiring any information about the eavesdropper channel and is suitable for practical applications. Another objective of the paper is the energy analysis of networks by taking into account processing and maintenance energy cost at the transmitters. We demonstrate that the combination of PA with an appropriate switch-off mechanism, that allows the source to transmit for an appropriate fraction of the time, significantly extends the network lifetime. All the proposed protocols are evaluated by theoretical and simulation results.